Hydraulic capacity extension of networks through the water savings and investment analysis approach (2025)
This study evaluates the water use efficiency (WUE) implementing under two approaches: i) reduction of water losses and the installation of low-consumption plumbing fixtures, and ii) Water savings analysis including, network Additional capacity, Reduction in per capita water consumption and the Investment (WARI). Hydraulic modeling was performed in the water distribution network of the campus of Universidad de Ibagué using EPANETv2.2, which supplies 5,172 people through 3,499.7 m of pipes during an analysis period of 48 months. The selection process for water-saving plumbing fixtures was carried out using the Analytical Hierarchy Process approach. The results indicate that WUE contributes to reducing water consumption by up to 47.8% and achieving a hydraulic capacity extension of the network of up to 67.0%, which is equivalent to extending pipes life cycle by up to 20 more years. WARI analysis is useful for water resource planners in decision-making processes within an economic and environmental sustainability framework.